Understanding the Relationship Between Diversity and Corporate Social Responsibility and its Contribution to Business in the Community's Corporate Responsibility Index - Conner, Hannah (2007)
The aim of this management report is to make recommendations on the way in which organisations could report more extensively on diversity within Business in the Community's Corporate Responsibility (CR) Index.